Pengembangan Paradigma Pendidikan Holistik: Sinergi Kurikulum Berbasis Cinta dan Pembelajaran AI & Coding - Ridwan; Saiful Akmal; Cut Yety Kasturi (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2026)
The rapid evolution of Artificial Intelligence (AI) and programming (coding) necessitates an innovative response from the educational sector to foster a generation that is not only digitally competent but also possesses strong character and ethics. This paper proposes a conceptual model to develop a holistic educational paradigm through the synergy between the Love-Based Curriculum (Kurikulum Berbasis Cinta or KBC) and AI & coding education within the madrasah environment. The objective is to bridge the gap between technological advancement and humanitarian values by establishing KBC as the ethical foundation for the development and utilization of technology. The methodology employed involves a literature analysis and synthesis to integrate the philosophical foundations of KBC, namely ontology, epistemology, and axiology, with the principles of AI ethics. The resulting model focuses on applying